2021
DOI: 10.1016/j.techfore.2021.121034
|View full text |Cite
|
Sign up to set email alerts
|

Online technology: Sustainable higher education or diploma disease for emerging society during emergency—comparison between pre and during COVID-19

Abstract: Even as the pandemic rages on across the globe, the notion of shutting down higher education has never been an option; instead, finding ways to circumvent it has led to a greater reliance on online technology delivery of courses and programs. Although this is not meant as a complete substitute, critics argue that online education has widened the ‘diploma disease’ crisis. They argued that this would lead to serious long-term problems which may become irreversible. This comparative study was conducted using an ‘… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 51 publications
0
25
0
2
Order By: Relevance
“…Students' academic scores were considered a predictor to identify the success of their education. Although sustainable education might cater to market popularity, online technology could ensure that the right knowledge and skills were put first for different modes of technology occurring in different situations [69]. Online technology could be useful for academic success, as it could easily make all students focus on online learning [2].…”
Section: Online Technology and A Sustainable Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Students' academic scores were considered a predictor to identify the success of their education. Although sustainable education might cater to market popularity, online technology could ensure that the right knowledge and skills were put first for different modes of technology occurring in different situations [69]. Online technology could be useful for academic success, as it could easily make all students focus on online learning [2].…”
Section: Online Technology and A Sustainable Educationmentioning
confidence: 99%
“…It was found that online-technology-based sustainable education might be the main tool for making money [69]. It could not ensure a sustainable education system for better educational development [105].…”
Section: The Role Of Online Technologymentioning
confidence: 99%
“…Chang et al, 2021;Rafiee & Abbasian-Naghneh, 2021). These results provide new reinforcement of the impact of covid-19, making students ready to prepare for the use of new technology; this is evidence to answer questions that have been made by (Alam & Asimiran, 2021;Winter et al, 2021). His research explained that students during the pandemic had better performance than prepandemic students, so the role of technology will positively impact the role of future teacher candidates, making the teaching and learning process more enjoyable (Danniels et al, 2020;Raja & Nagasubramani, 2018).…”
Section: Discussionmentioning
confidence: 63%
“…Educational technology choices make it difficult for educators to constantly update their knowledge, skills, and information from multiple sources and exacerbate educational inequalities (Tuma, 2021;Warden et al, 2020). Many developing countries, including Indonesia, cannot use the potential competitive advantage of technology, especially in education (Alam & Asimiran, 2021;Shohel & Kirkwood, 2012). These problems are examples of problems and challenges for students as aspiring future teachers ready for technologybased education.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation